What the Consequence Argument Is an Argument For. (23rd January 2019) - Capes, Justin A.
Abstract : The consequence argument is among the most influential arguments for the conclusion that free will and determinism are incompatible. Recently, however, it has become increasingly clear that the argument fails to establish that particular incompatibilist conclusion. Even so, a version of the argument can be formulated that supports a different incompatibilist conclusion, according to which free will is incompatible with our behavior being predetermined by factors beyond our control. This conclusion, though not equivalent to the traditional incompatibilist thesis that determinism strictly precludes free will, is something many incompatibilists have had in mind all along and, indeed, is arguably the more central incompatibilist position. The consequence argument thus remains philosophically important, even if, as several of its critics have argued, it can't be used to establish the strict incompatibility of free will and determinism.